Design and development of a lab scale bioreactor for heat inducible enzyme expression system - Adam, Daud; Ismail, Ahmad Faris; Mohd. Salleh, Hamzah (IIUM Press, 2011)
Bioreactors are very important for cell growth and mass production of intended product, for example enzyme. Considerations of the process such as the level of agitation, aeration without cell damage, temperature optimization, good control environment, cell concentration, optimized medium utilization must be taken into consideration. Design and selection for this design project depends on cell specific demand, regulatory and economics. In order to find the suitable bioreactor for instant temperature change, heat transfer and thermodynamics concept are implemented. Thus this project aspires to design an automated bioreactor system whereby its major function is both instantaneous heating and cooling for the production of a recombinant enzyme as the induction temperature is shifted from 37°C to 55°C and returning it back to 37°C. An extra controller which has similarities to the concept of heat exchanger is applied to the design of a lab scale bioreactor. The equipment is known to be twin thermo circulator. The higher the mass flow rate of the fluid from the twin thermo circulator contributes to high heat transfer, higher efficiency, and greater temperature change. The disadvantage is the higher the mass flow rate, the greater the pressure loss and a bigger pump is needed.